Evaluation of CKD-EPI and MDRD Prediction Equations for Estimation of GFR in Lean and Obese Bangladeshi Subjects - Saiedullah, M.; Begum, S.; Rahman, M. R.; Khan, M. A. H.; Hayat, S.; Kamaluddin, S. M.; Shaheen, M. A. H. (Journal of Scientific Research, 2012)
Glomerular filtration rate (GFR) is the filtrate produced by the kidneys in each minute. Chronic kidney disease epidemiology (CKD-EPI) and standardized modification of diet in renal disease (MDRD) equations are the commonly used equations to estimate GFR. Evaluation of GFR prediction equations regarding body mass index is not available in Bangladeshi population. In this study we compared estimated GFR (eGFR) with GFR measured by creatinine clearance rate (CCR) in lean and obese Bangladeshi subjects. Measured GFR were 40±21 and 45±22 ml/min/1.73m2 in lean and obese groups, respectively. Compared to measured GFR, estimated GFRs were 7.5 (p<0.0001), 5.2 (p<0.0001) ml/min/1.73m2 higher for CKD-EPI and MDRD four variables (MDRD4) equations in lean group and 6.9 (p<0.0001), 3.2 (p>0.05) ml/min/1.73 m2 higher for CKD-EPI and MDRD4 equations in obese group. The precision (r2) was 0.6461 for CKD-EPI, 0.6508 for MDRD4 equations in lean group and 0.6337 for CKD-EPI and 0.6021 for MDRD4 equations in obese group. The percentages of eGFR falling within 15% measured GFR were 37 for CKD-EPI, 52 for MDRD4 in lean group; 41 for CKD-EPI, 39 for MDRD4 in obese group. CKD-EPI equation overestimates GFR in both lean and obese, but MDRD4 equation overestimates GFR only in lean Bangladeshi subjects. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.8764 J. Sci. Res. 5 (1), 207-213 (2013)